Potential Applications of Nanocellulose-Containing Materials in the Biomedical Field - Halib, N; Perrone, F; Cemazar, M; Dapas, B; Farra, R; Abrami, M; Chiarappa, G; Forte, G; Zanconati, F; Pozzato, G; Murena, L; Fiotti, N; et al. (MDPI, 2024)
Because of its high biocompatibility, bio-degradability, low-cost and easy availability, cellulose finds application in disparate areas of research. Here we focus our attention on the most recent and attractive potential applications of cellulose in the biomedical field. We first describe the chemical/structural composition of cellulose fibers, the cellulose sources/features and cellulose chemical modifications employed to improve its properties. We then move to the description of cellulose potential applications in biomedicine. In this field, cellulose is most considered in recent research in the form of nano-sized particle, i.e., nanofiber cellulose (NFC) or cellulose nanocrystal (CNC). NFC is obtained from cellulose via chemical and mechanical methods. CNC can be obtained from macroscopic or microscopic forms of cellulose following strong acid hydrolysis. NFC and CNC are used for several reasons including the mechanical properties, the extended surface area and the low toxicity. Here we present some potential applications of nano-sized cellulose in the fields of wound healing, bone-cartilage regeneration, dental application and different human diseases including cancer. To witness the close proximity of nano-sized cellulose to the practical biomedical use, examples of recent clinical trials are also reported. Altogether, the described examples strongly support the enormous application potential of nano-sized cellulose in the biomedical field.